Impacto dos novos pontos de corte de sensibilidade nas taxas de resistência antimicrobiana de cepas invasivas de pneumococo recupera das de pacientes com pneumonia - Wolkers, Paula Carolina Bejo (2009)
The aim of this search was to evaluate the impact of penicillin and ceftriaxone new susceptibility breakpoints in reporting resistance of pneumococcus invasive strains obtained from patients hospitalized for pneumonia. Pneumococcus strains obtained from normally sterile fluids from pneumonic patients were isolated and identified at Uberlândia Federal University Clinical Analysis and forwarded to Adolfo Lutz Institute, in São Paulo, SP, for further identification, serotyping and antimicrobial susceptibility determination. From April 1999 to December 2008, 330 invasive pneumococcus strains were forwarded to Adolfo Lutz Institute. 195 of them were obtained from pneumonic patients. After exclusion of the invalid samples, 175 strains were analyzed: patients were from one to 86.8 years old (mean of 24.6 years and median of 4.4years), 89 (50.9%) male and the strains were isolated from blood (110 occasions [62.9%]) and pleural fluid (65 occasions [37.1%]). According to the former breakpoints to define penicillin susceptibility (minimum inhibitory concentration [MIC] ≤0.06g/mL for susceptible [S], 0.12 to 1g/mL for intermediate resistance [IR] and ≥2g/mL for plain resistance [PR]), there were 27 strains IR (15.4%) and 12 PR (6.9%) amongst 42 strains (24%) oxacillin-resistants. According to the new breakpointss (≤2g/mL for S, 4g/mL IR and ≥8g/mL for PR), only one strain showed resistance (RI) to penicillin. Decreased sensibility was detected to sulfamethoxazole-trimethoprim (64%), to tetracycline (17.1%), to erythromycin (8.6%), to clindamycin (8.6%) and to ofloxacin (0.6%). There was only one strain resistant (IR) to ceftriaxone, simultaneously resistant to penicillin. The isolates were all susceptible to chloranphenicol, rifampin and vancomycin. When the new criteria of breakpoints were applied, decreased susceptibility rate declined in 97.3%.